Tales of instability and decay: an integrable perspective - Ziółkowska, AA (2021)
This thesis presents theoretical groundwork for the investigation of particular phenomena of instability and decay in out-of-equilibrium many body systems. By employing mathematical methods of integrability, we succeed in gaining new insights into problems not traditionally associated with an integrable realm.